Hospital Charge Variability across New York State: Sociodemographic Factors in Pituitary Surgery - Kidwai, Sarah M.; Yang, Anthony; Gray, Mingyang L.; McKee, Sean; Iloreta, Alfred Marc; Shrivastava, Raj; Govindaraj, Satish (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Significant charge disparities exist across New York State (NYS). Race and income are associated with increased charges. To determine risk factor, we correlate hospital charges for pituitary surgery with socioeconomic factors. Additionally, we identify patients at risk for increased hospital charges and provide insight into cost-effective practices.Methods Retrospective cohort study of the Statewide Planning and Research Cooperative System (SPARCS) database from the NYS Department of Health was conducted. The SPARCS database was reviewed. Patients who underwent transsphenoidal pituitary surgery from 1995 to 2015 were identified. Income and urban status were referenced from U.S. census data. Linear regression was performed to analyze the effect of sociodemographic factors, comorbidities, and complications on hospital charges while controlling for length of stay.Results A total of 9,373 patients were identified. Black (10.8%, p < 0.001) and Asian (14.5%, p < 0.001) had higher hospital charges. Patients from nonurban cities (13.4%, p < 0.001), Medicaid (13.8%, p < 0.001), and those from the 0 to 25th (9.1%, p < 0.001) and 25 to 50th (11.7%, p < 0.001) income quartile had lower hospital charges. Patients with postoperative cerebrospinal fluid leak (24.0%, p < 0.001), diabetes insipidus (22.1%, p < 0.001), smoking history (11.8%, p < 0.001), hypertension (7.4%, p < 0.001), and hypothyroidism (6.9%, p < 0.001) had higher hospital charges.Conclusion Patients incurring higher chargers were more likely to have a smoking history, hypertension, hypothyroidism, and comorbidities. The determinants of this analysis may provide insight into barriers to patient access and cost improvement strategies. In addition, this emphasizes the need for future studies to create a risk stratification model, similar to those in other fields.
Keywords: rhinology; skull base; pituitary adenoma; charge variability; hospital costs